The study of long period gratings for improved refractive index sensing applications - Lim, Anthony (2014)
Fiber optical-based sensor system offers many distinctive advantages over conventional electrical-based sensor system such as immunity to EMI, the ability to multiplex sensors into complex networks and low cost. One of these fiber optical-based sensors is the Long Period Gratings (LPG) that has the advantage of higher sensitivity to the ambient Refractive Index (RI) change compared to the Fiber Braggs Gratings (FBG) which makes it a suitable sensor for many applications in chemical, biological and environmental measurement and test. Many different configurations of LPG on a Single Mode Fiber (SMF) had been developed with the highest sensitivity of 506.9nm/ RIU reported for a post-etched LPG with 810 tilted gratings written into it. There are other studies to introduce coatings to the cladding of the LPG using gold nano-rods, SiO2 nano-particles to increase the sensitivity but it has trade-offs, one of which is the increase in the process steps and complexity with the additional materials coated onto the LPG cladding surface which increases the fabrication cost. In the first part of this study, the LPG with Regular Corrugations on its Cladding was developed and characterized with an improved sensitivity of 611nm/ RIU, compared to the other LPG sensors developed before. Using the CO2 laser, corrugations on the LPG cladding was formed which encourages the interaction of the evanescent wave with the surrounding environment. With the control of the CO2 laser beam power and speed, different corrugation depths and periods were fabricated and their effects on the LPG sensitivity were characterized. The effect of the corrugation periods on the resonance wavelength of the LPG was also studied. The study showed that the variation of corrugation depth changes the sensitivity of the sensor to the ambient RI while the changes in the corrugation period do not have any effect on the sensor sensitivity. On the other hand, the variation of the corrugation depth do not change the resonance wavelength significantly while the changes in the corrugation periods will caused a shift in the resonance wavelength. The experimental results show that this corrugated cladding LPG structure has good performances in terms of linearity and sensitivity to ambient RI changes while it can also serve as a cost effective sensor. The innovative dual use of the corrugations to improve the LPG sensitivity, also served as a reservoir to collect and hold the specimen for testing. This sensor has the advantages of high sensitivity, small feature size, compact, ease of use and offers potential use in various chemical and biological sensing applications in the future. With the in-fiber corrugations that serve also as the collection reservoir, it can also be deployed as an onsite sensor to collect specimen for measurement and disposed thereafter due to its low cost. In the second part of the study, the LPG with Controllable Refractive Index Sensitivity involves the innovative use of the semiconductor process, Reactive Inductive Etch (RIE) to accurately etch the cladding of the LPG sensor to the design requirements of the application. In past studies, reducing the cladding of the LPG using the chemical etch was the standard process used where the cladding is etched with the diluted 12% Hydrofluoric Acid (HF), achieving an etching rate of 20μm/min. This inhibited the development of an accurately designed LPG sensor on a 125μm SMF. However, the use of RIE with the smaller etch rate of 46nm/min allowed the development of LPG sensor with accurate RI ambient sensitivity. The effect of the different parameters in the RIE process, CF4, O2, Radio Frequency (RF) and chamber pressure on the etching of LPG cladding was studied. The results showed that the RIE process can effectively reduce the LPG cladding thickness with a resolution of 46nm and does not damage the functionality of the LPG. The study also showed that controlling the time of the RIE etch process, different LPG cladding thickness can be developed within the desired sensitivity. The characterization showed good system performances such as linear responses, good repeatability and low hysteresis, which is important for its use in industrial applications and where it has to operate in harsh environment. As a result, with the RIE process, fiber-based LPG sensor can be designed to the required sensitivity and integrated as a sensor into the silicon substrate platform to form the Lab-On-A-Chip (LOC) kit using the well-established RIE semiconductor process. Together with deposition, photolithography and etch processes, RIE can be used to fabricate the optical source and detector on the same silicon substrate platform while it can also be simultaneously used to trim the fiber-based LPG to the designed sensitivity so that it can function as an onboard ambient RI sensor in the LOC system.